恐怕是ab不为0,
那么lim(f(x+aΔx)-f(x-bΔx)/Δx
=lim(f(x+aΔx)-f(x)+f(x)-f(x-bΔx))/Δx
=lim(f(x+aΔx)-f(x))/Δx+lim(f(x)-f(x-bΔx))/Δx
=lima(f(x+aΔx)-f(x))/aΔx+limb(f(x-bΔx)-f(x))/(-bΔx)
=af'(x)+bf‘(x)嗯,这个如果ab不等于的话我是知道怎么做的,就是卡在ab=0这上面。书上说ab=0的情况下结果是一样的。设ab=0,那么a=0,b不为0或者b=0,a不为0或a=b=0若b=0,那么lim(f(x+aΔx)-f(x-bΔx)/Δx=lim(f(x+aΔx)-f(x))/Δx=lima(f(x+aΔx)-f(x))/aΔx=af'(x)若a=0,那么lim(f(x+aΔx)-f(x-bΔx)/Δx=-lim(f(x-bΔx)-f(x))/Δx=blima(f(x-bΔx)-f(x))/(-bΔx)=bf'(x)若a=b=0,lim(f(x+aΔx)-f(x-bΔx)/Δx=0所以:lim(f(x+aΔx)-f(x-bΔx)/Δx=af'(x)+bf‘(x)